IT governance: status and level of implementation in Zimbabwean urban local authorities - Mamboko, Patrick; Zhou, Munyaradzi; Tsokota, Theo; Mhaka, Charity (European Journal of Business and Management, 2019)
Information Technology has become an indispensable tool in enabling business processes. The study sought to assess the status and level of implementation of IT governance in Local authorities in Zimbabwe. Three local authorities were used as case studies and respondents were purposively selected from Councillors of the three local authorities . Interviews were then conducted with senior personnel; Chamber Secretary, Town Clerk and the Treasurer. In order to assess the status and level of implementation, reference was made to the Institute of Information technology (ITGI) governance framework. It was discovered that, the Local authorities in Zimbabwe’s IT functions are not aligned to business strategies. Urban Local authorities in Zimbabwe need to properly take on board IT in order to improve service delivery.